Profiles of neurobehavior and their associations with brain abnormalities on MRI in infants born preterm. (June 2020) - Kennedy, Eleanor; Wouldes, Trecia; Perry, David; Deib, Gerard; Alsweiler, Jane; Crowther, Caroline; Harding, Jane; ,
Highlights: In preterm infants, measures of neurobehavior and brain abnormalities are related. Deep grey matter abnormalities are associated with altered neurobehavior. Neurobehavioral scores clustered into two distinct profiles. An even-tempered profile was associated with cortical grey matter abnormalities.